SYSTEM ANALYSIS TO PROVIDE THE ACHIEVEMENT OF TWO MILLION TONS SURPLUS OF RICE PRODUCTION THROUGH 2014 IN NUSA TENGGARA BARAT - I Putu Cakra Adnyana; M. Nazam (Socio-Economics/Agribusiness Department, 2016)
Until now, rice is still the staple food for more than 95% of NTB people and has high sensitivity towards political, economic and social issue. Challenge that faced in this food supply is lesser land area, both its wide and quality due to continuous conversion of agricultural land to non-agricultural use. Rice supply system is a complex system because it involves multiple sectors and covers many aspects. To solve the problem, it is required more comprehensive and holistic approach. This study aims to analyze rice supply system to the achievement of 2 million tons surplus of rice production through 2014 in NTB. Data in this research was collected by survey, FGD, consultation, observation and desk study. Analysis in this research used dynamic system. The result showed that rice self-sufficiency could be achieved if it is accompanied by assessment to increase rice productivity and supporting policy where there will be no expansion and no conversion of wetland or paddy field area at NTB in 2014. The government should immediately establish the policy to introduce new rice varieties, which potentially can yield 8 tons rice/ha, 5% grain loss and 2.5% rice loss through harvest tools and post harvest process. It should also be accompanied by IP (cropping index) score increase to 1.94 per year through 30% irrigation improvement and balanced fertilization. Rice crop should be improved by 1.146, 75% balanced fertilization, 75% seeds quality improvement and 75% decrease of pests and plant diseases. In addition, the government is necessary to establish regulations which governing responsibility between government, private sector and farmer in order to achieve IDR 208 billions budget in 2014.